Penerapan Lean Thinking untuk Mereduksi Waktu Boarding Pasien IGD ke Rawat Inap di RSUD Koja Tahun 2017 - Theryoto, Theryoto (UI Scholars Hub, 2017)
The implementation of the National Health Insurance Program (Program JKN) affects the increased number of patients to emergency unit and boarding patients that resulting crowding in the emergency unit. Koja Hospital has implemented bed management in order to reduce the boarding time of emergency unit patients but has not succeeded, so an effort to help reducing the boarding time of emergency unit patients to inpatient in order to continuous improvement was done using the lean thinking principle. This research uses operational research method and intervention with PDCA (Plan, Do, Check, Action) cycle. The study revealed that lean thinking approach could reduce the boarding time of emergency unit patients to hospitalization from the average of 4 hours 45 minutes 18 seconds (34.92%) to 3 hours 25 minutes 59 seconds (68.25%) and decrease the activity of non value added at 2.02% (from 93.16% to 91.14%). Eight types of waste identified can be eliminated except waiting. In order to continuous improvement, bed management should be set as standardized work for the goal of average boarding time of 1 hour 45 minutes 45 seconds with non value added activities less than 89.83% in the future.